Body weight and body height assessment in male high school seniors - Berisha, Ajvaz; Koca, Afrim (Journal of Education, Health and Sport, 2018)
The purpose of this research was to be evaluated the body weight and body height in male high school seniors. A total measured samples participated in this research was 142 out of who had an average age of 18.27 ± 0.47. (range 18-20 years). The anthropometric measurements of body weight and body height according to the protocol of the International Biological Society (IBP). The measurements were conducted by a group of experts of the Faculty of Physical Education and Sports in Prishtina. The results obtained from the measurements are processed with the SPSS program for windows 20.00. The data obtained were analyzed through the descriptive parameters (Minum and Maximum, Arithmetic Average, Standard deviation and Skewnews & Kurtosis). Relationships between body weight and body height were analyzed by Pearson correlation coefficient with an accuracy level of 95%. In order to predict the assessment of body weight results with the body's height variable, linear regression analysis method has been utilized. For all results the validity rate is p <0.5. As a result anthropometric measurements for male high school senior showed that the average of Body weight are 73.98±11.20 kg and the body height average of 179.39±6.37centimeters.The results have shown that body weight is estimated as a reliable indicator of body height evaluation, the male seniors from high school from the region of Gjakova population. This study also confirms the need for developing different height and weight models for each region in Kosovo.